(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ion exchange polymers are widely used in various fields of science and technology. In this regard, the requirements made by the industry for their thermo-chemical resistance, mechanical strength and selectivity are increasing. Such universal ion-exchange resins as KU-2, KU-1, SHS, etc. no longer meet many of these requirements. Despite the fact that they have high kinetic and sorption properties [1]. Phosphorus-containing ion exchangers [2] have a special place among the known ion exchangers from a physicochemical point of view. These ion exchangers have a number of valuable properties: high selectivity, heat resistance, mechanical strength, etc. [3] These properties determine the prospects for the use of these ion exchangers in various areas of the national economy and industry. Based on the foregoing, by phosphorilation the polymer obtained by polycondensation of bottoms waste of the Shurtan gas chemical complex with the secondary raw material of the hydrolysis industry with furfural, we obtained a phosphate cation exchanger. [3].